2015
DOI: 10.1186/s12864-015-2036-9
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput mRNA and miRNA profiling of epithelial-mesenchymal transition in MDCK cells

Abstract: BackgroundEpithelial-mesenchymal transition (EMT) is an important process in embryonic development, especially during gastrulation and organ formation. Furthermore EMT is widely observed in pathological conditions, e.g., fibrosis, tumor progression and metastasis. Madin-Darby Canine Kidney (MDCK) cells are widely used for studies of EMT and epithelial plasticity. MDCK cells show an epithelial phenotype, while oncogenic Ras-transformed MDCK (MDCK-Ras) cells undergo EMT and show a mesenchymal phenotype.MethodsRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 98 publications
(120 reference statements)
0
23
0
Order By: Relevance
“…To clarify the roles of claudin-based TJ strands in epithelial polarity, we generated claudin quinKO cells by sequentially knocking out the five major claudins expressed in MDCK II cells (claudin-2, claudin-4, claudin-3, claudin-7, and claudin-1, in that order, based on the RNA sequencing dataset reported by Shukla et al, 2015). Two independent claudin quinKO cell clones were generated, and Sanger sequencing revealed that claudin quinKO cells harbored frameshift mutations for claudin-2, claudin-4, claudin-3, and claudin-7 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To clarify the roles of claudin-based TJ strands in epithelial polarity, we generated claudin quinKO cells by sequentially knocking out the five major claudins expressed in MDCK II cells (claudin-2, claudin-4, claudin-3, claudin-7, and claudin-1, in that order, based on the RNA sequencing dataset reported by Shukla et al, 2015). Two independent claudin quinKO cell clones were generated, and Sanger sequencing revealed that claudin quinKO cells harbored frameshift mutations for claudin-2, claudin-4, claudin-3, and claudin-7 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This could allow expression of genes that were turned off in a previous developmental step. Some possibilities of ways in which EMT might accomplish this include opening chromatin (McDonald et al, 2011), direct gene expression effects leading to signaling changes (Cie slik et al, 2013), and modifying post-transcriptional control of gene expression (Shukla et al, 2015;Unternaehrer et al, 2014).…”
Section: Resolution: Emt Results In Transient Dedifferentiation Allowmentioning
confidence: 99%
“…1c lower-panel). The up-regulation of miR-133a was particularly interesting because previous studies had shown its up-regulation in small airway epithelium of smokers 20 as well as Madin-Darby Canine Kidney (MDCK) epithelial cells undergoing EMT 29 , 30 . Results from real-time PCR indicated that the expression level of miR-133a in mesenchymal-like Beas-2b/M cells was 10-fold higher than that of normal epithelial-like Beas-2b cells (Fig.…”
Section: Resultsmentioning
confidence: 99%